Kinesiotaping Diminishes Delayed Muscle Soreness but does not Improve Muscular Performance - Camacho, Maria Alejandra; Herrera, Esperanza; Barela, Jose Angelo [UNESP]; Delgado-Diaz, Diana Carolina (Georg Thieme Verlag Kg, 2020)
This study aimed at determining the effect of kinesio-taping (KT) on muscle performance and delayed onset muscle soreness (DOMS) after exercise induced muscle damaged. Sixty-six healthy men volunteered to participate (age:18-25 y/o), who performed 200 isokinetic lengthening contractions of the dominant quadriceps. Then subjects were randomized to either control (no treatment), sham (no tape tension), or KT (10% tape tension) groups. Muscle performance was assessed by peak torque and muscular work during maximal isometric and concentric isokinetic contractions. DOMS intensity was assessed using a visual analog scale. Measurements were taken pre-exercise (Pre), 48 h and 96 h post-exercise. Repeated measures ANOVA was used for comparisons within group, and ANCOVA for comparisons among groups. Muscle damage was confirmed in all participants by an increase in CK activity level (p<0.01). Decrease in isometric and isokinetic peak torque was detected at 48 h in the control and sham groups (p<0.01). Muscular work decreased in all groups at 48 h (p<0.01). No differences between groups were detected in muscular performance variables. Increase in DOMS intensity was determined in all groups at 48 h. Comparisons between groups showed lower DOMS intensity in the KT group at 48 h. KT decreased DOMS intensity perception after exercise-induced muscle damage; however, it did not impact muscular performance.
Keywords: kinesio-taping; muscle injuries; muscle performance; delayed onset muscle soreness